POLÍTICAS DE FINANCIAMENTO E DE VALORIZAÇÃO DOS PROFISSIONAIS DA EDUCAÇÃO: UMA ANÁLISE DO PLANO DE CARREIRA DO MAGISTÉRIO DO MUNICÍPIO DE PAULA FREITAS - PR - LUCYK, VIVIANA PATRICIA KOZLOWSKI (2019)
This research seeks to analyze the correspondence between education funding policies and policies that announce the valorization of education professionals. This theme that gains prominence from the debates generated in the period of elaboration of the Fund for the Maintenance and Development of Elementary Education and Valorization of the Magisterium (FUNDEF) and the National Education Plan (PNE) of 2001, and intensifies in the debates of preparation of the Fund for the Maintenance and Development of Basic Education and Valorization of Education Professionals (FUNDEB) and the National Education Plan (PNE) 2014. In this context it is verified that the correspondence between funding and teacher valuation is not resolved, and that there are many doubts involving the theme. So we seek, in this study, to answer the following questions: How the teaching career is addressed in the documents and recommendations of international bodies? How does funding develop over time in the field of policies? How does education funding in current legislation happen? What are the main concepts and conceptions of teacher appreciation? What are the strategies of current legislation to ensure teacher appreciation? How does the academic environment deal with the relationship between education funding and teacher appreciation? What have been the advances and setbacks resulting from the implementation of financing policies? Has the teacher appreciation been performed through the financing of education in the municipality of Paula Freitas - PR? The central objective of the work is to analyze to what extent public policies and educational financing strategies contributed to the teaching valorization process in the municipality of Paula Freitas - PR. First, it seeks to present the reality of municipality under study, of which we formulateour object of study. At the second moment, it seeks to identify how the teaching career is addressed in the documents and recommendations of international organizations. It also conducts a bibliographic survey on the history of education funding in Brazil and analyzes the current legislation on the subject. In the third moment it presents the meanings of teacher valorization, its concepts and terminologies. It also examines what the legal bases discuss about the appreciation of the teacher today. Finally, it portrays the organization of education and application of educational resources in the municipality of Paula Freitas from 2005 to 2017, and analyzes, from a socio-historical perspective, the policy of valuing education professionals in the dimensions of the Financing. It was possible to identify: 1) that Brazilian education, around the 1990s, underwent changes from state reform, and neoliberal conception invaded the school, which began to be regulated as merchandise and its management follows the business model; 2) fund policy, FUNDEF (1996-2006) and FUNDEB (2007-2020), is also the result of state reform and thus funding corresponds to the requirements of this reform for streamlining public spending; 3) that the relationship between funding and teacher appreciation is full of resistance and clashes, and there is still a long way to go so that funding is able to generate teacher appreciation.